INTEGRASI TEKNOLOGI PENDIDIKAN DALAM PEMBELAJARAN TATAP MUKA TERBATAS: STUDI PENGEMBANGAN MODEL HYBRID LEARNING DI SMAN 1 TALIWANG - Fahri Hamdani; Dinola, Dinola; Anwar, Anwar (Yayasan Nusantara Hasana Berdikari, 2025)
This study examines the implementation of a hybrid learning model in limited face-to-face instruction at SMAN 1 Taliwang, developed as an adaptive response to post-pandemic learning conditions. Using a Research and Development (R&D) approach based on the ADDIE model, data were collected through classroom observations, questionnaires for teachers and students, and analysis of pre-test and post-test learning outcomes. The findings indicate that integrating digital tools—such as Google Classroom, video-based materials, and digital modules—helped maintain learning continuity despite reduced classroom hours. Most students reported that digital media facilitated their understanding of the material, although some still faced internet access challenges, particularly those living in peripheral areas of Taliwang. The results show significant improvements in student learning processes and outcomes. The average post-test scores increased compared to the pre-test, and student participation in submitting digital assignments exceeded 85%. Teachers also stated that the hybrid learning model provided greater flexibility in delivering materials and conducting assessments. Although the model did not fully resolve all technical issues and variations in students’ digital literacy, it proved feasible and effective as an adaptive learning strategy at SMAN 1 Taliwang. These findings support the continued refinement and long-term integration of educational technology within the school’s instructional practices.